2011
DOI: 10.3164/jcbn.11-22
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate enhancement of inteleukin-1β production via activation of oxidative stress pathways in lipopolysaccharide-stimulated THP-1 cells

Abstract: In inflammatory bowel diseases, interleukin-1β production is accelerated. Butyrate, a short chain fatty acid, plays an important role in inflammatory bowel diseases. We investigated the effect of butyrate on interleukin-1β production in macrophage and elucidated its underlying mechanism. We stimulated THP-1 cells, a human premonocytic cell line, by lipopolysaccharide alone and by butyrate with lipopolysaccharide. Butyrate with lipopolysaccharide increased interleukin-1β production more than lipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…It was in line with the previous study which states that a high fiber diet can reduce inflammatory responses characterized by lower IL-1β [24]. It was suspected to be due to SCFA contents, especially butyrate, one of the results of fermentation of food fiber, suppressing cytokines which stimulate the production of inflammatory mediators such as IL-1β [25]. The main mechanism which could explain the effect was reduced HDAC activity [26].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was in line with the previous study which states that a high fiber diet can reduce inflammatory responses characterized by lower IL-1β [24]. It was suspected to be due to SCFA contents, especially butyrate, one of the results of fermentation of food fiber, suppressing cytokines which stimulate the production of inflammatory mediators such as IL-1β [25]. The main mechanism which could explain the effect was reduced HDAC activity [26].…”
Section: Discussionsupporting
confidence: 90%
“…Short chain fatty acids worked with cytokines in leukocytes and endothelial cells through two mechanisms, i.e. GPR activation HDAC inhibition [25]. Short chain fatty acids regulated cytokine production, including IL-1β [13].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we also acknowledge the possibility that co-culture induces the initial production of inflammatory mediators, followed by lipolysis 6) . On the other hand, we previously demonstrated that butyrate enhances IL-1β production via the activation of oxidative stress pathways in lipopolysaccharidestimulated THP-1 cells 38) . Although the culture condition in the previous study is different from the present study, butyrate appears to have acceleratory or inhibitory effects on the macrophage-mediated inflammatory response.…”
Section: Acknowledgementsmentioning
confidence: 88%
“…However, no signs of inflammation were seen in livers of these control mice. In in vitro studies of Ohira et al ( 28 ) , it was shown that an incubation of macrophages with butyrate especially in the presence of endotoxin is associated with an increased expression of IL-1β . Furthermore, Mattace et al ( 6 ) also reported a non-significant approximately 2-fold increase in IL-1β expression and cyclo-oxygenase-2 (COX-2) protein levels in livers of control rats fed a diet enriched with butyrate (20 mg/kg body weight).…”
Section: Discussionmentioning
confidence: 99%